PENGARUH PENERAPAN E-FILLING, PERSEPSI WAJIB PAJAK DAN PENGALAMAN PENGGUNAAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM PENYAMPAIAN SURAT PEMBERITAHUAN TAHUNAN DI KANTOR PELAYANAN PAJAK PRATAMA KUPANG - Elsya Stivani Monica Ndaumanu; Anthon S. Y. Kerihi; Cicilia A. Tungga (Bajang Institute, 2026)
This study aims to determine (1) To determine and analyze the effect of the implementation of E-filling on the Compliance of Individual Taxpayers in submitting Annual Tax Returns. (2) To determine and analyze the effect of the perception of Taxpayer convenience on the Compliance of Individual Taxpayers in submitting Annual Tax Returns. (3) To determine and analyze the effect of the experience of using E-filling on the compliance of Individual Taxpayers in submitting Annual Tax Returns. (4) To determine the effect of the implementation of E-filling, taxpayer perceptions and experience of using E-filling on the compliance of individual taxpayers in submitting annual tax returns at the Kupang Pratama Tax Service Office. The data used in this study were obtained using a questionnaire. This study uses a quantitative research approach. The population in this study were individual Taxpayers who reported SPT via E-filling at the Kupang Pratama Tax Office in 2024 totaling 54,587 Taxpayers. The sample of this study was 100 Taxpayers at the Kupang Pratama Tax Office in 2024. Sampling in this study used the Slovin formula. The analysis method used was descriptive statistical analysis, validity test, reliability test, classical assumption test, multiple linear regression and hypothesis test using the statistical package for the social sciences 25 (SPSS 31) application. The results of this study indicate that (1) The Implementation of E-Filling has a significant effect on Individual Taxpayer Compliance in submitting Annual Tax Returns at the Kupang Pratama Tax Service Office. (2) Taxpayer Perception has a significant effect on the ease of use of e-filling in reporting SPT. (3) Experience in using e-filling has a significant effect on Individual Taxpayer compliance. (4) The Implementation of E-filling, Perception of Ease of Use of Taxpayers and Experience in Using E-filling together have a significant effect on Taxpayer Compliance in Submitting Annual Tax Returns.